2021
DOI: 10.1111/jdi.13522
|View full text |Cite
|
Sign up to set email alerts
|

Association of plant‐based diet and type 2 diabetes mellitus in Chinese rural adults: The Henan Rural Cohort Study

Abstract: Aims/Introduction: Studies have found that a plant-based diet was associated with a lower risk of type 2 diabetes, but evidence is scarce on such associations in China. The aim of this study was to investigate whether a plant-based diet is related to a lower risk of type 2 diabetes among Chinese adults. Materials and Methods: A total of 37,985 participants were enrolled from the Henan Rural Cohort Study. An overall plant-based diet index (PDI) was created by assigning positive and reverse scores to 12 commonly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…Our study also suggests that high intake of plant protein appears to reduce the risk of T2DM, which is similar to previous observational studies (12,13,36). However, the Melbourne Collaborative Cohort Study (37) and the European studies (11,29) showed no significant association of plant protein intake with T2DM risk.…”
Section: Discussionsupporting
confidence: 91%
“…Our study also suggests that high intake of plant protein appears to reduce the risk of T2DM, which is similar to previous observational studies (12,13,36). However, the Melbourne Collaborative Cohort Study (37) and the European studies (11,29) showed no significant association of plant protein intake with T2DM risk.…”
Section: Discussionsupporting
confidence: 91%
“…Previous prospective studies and meta-analyses have concluded that higher PDI and hPDI scores are negatively associated with lower reductions in weight gain over 4-year intervals (10). Plantbased diets, especially those rich in high-quality plant foods, significantly reduce the risk of T2D (9,13,(33)(34)(35). PDI or hPDI Adjusted for age, urban and rural, sex, total energy intake, education, physical activity, smoking status, alcohol drinking, baseline systolic and diastolic blood pressure, and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…It also showed that fructosamine level dropped signifi cantly. In the study conducted by Yang et al (2021), they stated that they believed a plant-based diet would overcome to some extent infl ammation and insulin secretion and improve blood glucose control. This can reduce the risk of T2DM.…”
Section: Blood Glucosementioning
confidence: 99%
“…In addition to being high in fi ber, plant-based foods also contain antioxidants, like polyphenol, which can trigger insulin secretion by inhibiting the absorption of glucose in the intestine. It causes decreased postprandial glycemic response and increased insulin sensitivity (Yang et al, 2021).…”
Section: Hormonementioning
confidence: 99%